Associations of sodium and potassium consumption with the gut microbiota and host metabolites in a population-based study in Chinese adults. Issue 6 (6th October 2020) - Wang, Yiqing; Wang, Huijun; Howard, Annie Green; Tsilimigras, Matthew C B; Avery, Christy L; Meyer, Katie A; Sha, Wei; Sun, Shan; Zhang, Jiguo; Su, Chang; Wang, Zhihong; Zhang, Bing; et al.
ABSTRACT: Background: There is increasing evidence that sodium consumption alters the gut microbiota and host metabolome in murine models and small studies in humans. However, there is a lack of population-based studies that capture large variations in sodium consumption as well as potassium consumption. Objective: We examined the associations of energy-adjusted dietary sodium (milligrams/kilocalorie), potassium, and sodium-to-potassium (Na/K) ratio with the microbiota and plasma metabolome in a well-characterized Chinese cohort with habitual excessive sodium and deficient potassium consumption. Methods: We estimated dietary intakes from 3 consecutive validated 24-h recalls and household inventories. In 2833 adults (18–80 y old, 51.2% females), we analyzed microbial (genus-level 16S ribosomal RNA) between-person diversity, using distance-based redundancy analysis (dbRDA), and within-person diversity and taxa abundance using linear regression, accounting for geographic variation in both. In a subsample ( n  = 392), we analyzed the overall metabolome (dbRDA) and individual metabolites (linear regression). P values for specific taxa and metabolites were false discovery rate adjusted ( q -value). Results: Sodium, potassium, and Na/K ratio were associated with microbial between-person diversity (dbRDA P  < 0.01) and several specific taxa with large geographic variation, including pathogenic Staphylococcus and Moraxellaceae, and SCFA-producing Phascolarctobacterium and Lachnospiraceae ( q -value < 0.05). For example, sodium and Na/K ratio were positively associated with Staphylococcus and Moraxellaceae in Liaoning, whereas potassium was positively associated with 2 genera from Lachnospiraceae in Shanghai. Additionally, sodium, potassium, and Na/K ratio were associated with the overall metabolome (dbRDA P  ≤ 0.01) and several individual metabolites, including butyrate/isobutyrate and gut-derived phenolics such as 1, 2, 3-benzenetriol sulfate, which was negatively associated with sodium in Guizhou ( q -value < 0.05). Conclusions: Our findings suggest that sodium and potassium consumption is associated with taxa and metabolites that have been implicated in cardiometabolic health, providing insights into the potential roles of gut microbiota and host metabolites in the pathogenesis of sodium- and potassium-associated diseases. More studies are needed to confirm our results.